2021
DOI: 10.3390/polym13213832
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ionomer Content in the Catalytic Layer of MEAs Based on Aquivion® Ionomer

Abstract: Perfluorinated sulfonic acid (PFSA) polymers such as Nafion® are widely used for both electrolyte membranes and ionomers in the catalytic layer of membrane-electrode assemblies (MEAs) because of their high protonic conductivity, σH, as well as chemical and thermal stability. The use of PFSA polymers with shorter side chains and lower equivalent weight (EW) than Nafion®, such as Aquivion® PFSA ionomers, is a valid approach to improve fuel cell performance and stability under drastic operative conditions such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The catalytic ink was deposited by spray coating technique onto a commercial gas diffusion layer Sigracet-24 BC (from the SGL group). The catalytic ink was obtained by mixing the electrocatalyst, with 33 wt% of dry Nafion ionomer (5 wt% hydro-alcoholic solution IonPower-LQ1105), and 20 wt% of ammonium carbonate that acts as a pore-former, as described elsewhere [37,38]. For the cathode, a 40% Pt/C (Alfa Aesar) as electrocatalyst and the Pt loading 0.5 mg cm -2 was used.…”
Section: Electrodes Used and Membrane Electrode Assembly Integrationmentioning
confidence: 99%
“…The catalytic ink was deposited by spray coating technique onto a commercial gas diffusion layer Sigracet-24 BC (from the SGL group). The catalytic ink was obtained by mixing the electrocatalyst, with 33 wt% of dry Nafion ionomer (5 wt% hydro-alcoholic solution IonPower-LQ1105), and 20 wt% of ammonium carbonate that acts as a pore-former, as described elsewhere [37,38]. For the cathode, a 40% Pt/C (Alfa Aesar) as electrocatalyst and the Pt loading 0.5 mg cm -2 was used.…”
Section: Electrodes Used and Membrane Electrode Assembly Integrationmentioning
confidence: 99%
“…Another motivation for a comprehensive design of the catalyst layer is that the nature and loading of the ionomer can severely impact the electrode morphology and reactant transport. [130][131][132][133][134][135][136][137][138] Molecular dynamics simulations and TEM observations have shown that ionomers tend to deposit in the form of thin films on the surface of platinum-based catalysts. [139] The morphology of Pt/C-based electrodes has also been reported to depend on the ionomer content, when using the commercial anion exchange ionomer Tokuyama AS-4.…”
Section: Electrode Morphologymentioning
confidence: 99%
“…Various studies have shown how the choice of AEI can impact the morphology of the catalyst layer and, for the case of platinum, particle aggregation. [89,130,146,[148][149][150][151][152][131][132][133][134][135][136][137][138] However, very limited work has been dedicated to the effect of anion exchange ionomers on the deposition of transition metal catalysts, which tend to have higher surface area and larger particle size than platinum. Therefore, further investigation should be dedicated to optimizing the ionomer composition and ink formulation for PGM-free catalysts.…”
Section: Catalyst Layer Morphologymentioning
confidence: 99%
“…PEMs are considered as an efficient PEM for DMFCs due to their high proton conductivity, lower methanol permeability and oxygen, easier availability, low cost, high chemical stability, efficient electrochemical steadiness, and higher mechanical and thermal stability [ 63 , 64 , 65 ]. The commercial polymer membranes (such as DuPont (Nafion ® ), Asahi Glass Engineering (FlemionR ® ), Fumatech (Fumion ® ), Solvay (Aquivion ® ), Asahi Kasei (Aciplex-S ® ), and Dow Chemicals (XUS ® )) have been effectively considered as PEMs [ 63 , 65 , 66 , 67 , 68 ]. Perfluorosulfonic acid (PFSA) contains two hydrophobic and hydrophilic phases, where the polymer backbone is the hydrophobic phase and the side chain containing the sulfonic acid functional group is the hydrophilic phase [ 69 , 70 , 71 , 72 ].…”
Section: Introductionmentioning
confidence: 99%